2022
DOI: 10.1021/acs.chemmater.2c01533
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Driven Phase Transition in Two-Dimensional Perovskite MHy2PbBr4

Abstract: The application of high pressure allows tuning physicochemical properties of materials by changing interatomic distances. Pressure may also induce structural phase transitions into new phases with enhanced or novel functional properties. Here, we report complementary high-pressure single-crystal X-ray diffraction, Raman spectroscopy, and optical studies of a two-dimensional (2D) perovskite, MHy 2 PbBr 4 , comprising a very small spacer cation (methylhydrazinium, MHy + ). This crystal exhibits highly desired fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
55
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 71 publications
9
55
1
Order By: Relevance
“…The broadband emissions with large Stoke shifts are usually attributed to self-trapped excitons (STEx). 27,[68][69][70][71][72] Stability of STEx states increases with the enhancement of exciton-phonon coupling, and numerous studies showed that the intensity of STEx PL and Stokes shift increase with increasing distortion of the inorganic layers (decreasing y link ). 27,68,72,73 Since the high level of structural distortions is typical of (110)-oriented perovskites, 36,46,53 these compounds often show STEx related broadband emission, including the white-light one.…”
Section: Optical Studiesmentioning
confidence: 99%
“…The broadband emissions with large Stoke shifts are usually attributed to self-trapped excitons (STEx). 27,[68][69][70][71][72] Stability of STEx states increases with the enhancement of exciton-phonon coupling, and numerous studies showed that the intensity of STEx PL and Stokes shift increase with increasing distortion of the inorganic layers (decreasing y link ). 27,68,72,73 Since the high level of structural distortions is typical of (110)-oriented perovskites, 36,46,53 these compounds often show STEx related broadband emission, including the white-light one.…”
Section: Optical Studiesmentioning
confidence: 99%
“…However, in our powder X-ray diffraction (PXRD) measurements using silicone oil as the PTM, the second-order Birch–Murnaghan equation of state demonstrates B 0 of 27.9(9) GPa with B ′ of 4.0 in phase II, which is almost 2 times larger than that in the PTM of the ME mixture, implying that the [Ni­(en) 3 ]­(ox) single crystal is extremely sensitive to the hydrostatic environment. Such character has been observed in most of the soft materials, such as coordination polymers , and hybrid perovskites. …”
mentioning
confidence: 96%
“…Studies of 2D halide perovskites were undertaken by a number of different groups, making advances in their design broadly. For example, Solis-Ibarra and co-workers showed that the broadband emission of these materials could be enhanced through a combination of halide bonds and halide mixing while the application of pressure can induce phase transitions and, in turn, modulate optical properties as shown by a multicountry collaboration lead by Katrusiak …”
mentioning
confidence: 99%
“…Thus, it is not surprising that other recent manuscripts highlight materials with potential energy and light-emitting/phosphor applications. Organic, hybrid, and inorganic materials have been the focus of these studies, with a recent review on dual-state emission in organic fluorophores . Studies of 2D halide perovskites were undertaken by a number of different groups, making advances in their design broadly.…”
mentioning
confidence: 99%
See 1 more Smart Citation